Ginsenoside Rh2 Inhibits Migration of Lung Cancer Cells under Hypoxia via mir-491 - Chen, Yingying; Zhang, Yuqiang; Song, Wei; Zhang, Ying; Dong, Xiu; Tan, Mingqi (Anti-Cancer Agents in Medicinal Chemistry, 2019)
Background: Ginsenoside Rh2 (Rh2), which is extracted from ginseng, exerts antitumor activity. Here we would like to study the role of Rh2 on hypoxia-induced migration in lung adenocarcinoma. Methods: Lung adenocarcinoma A549 and H1299 cells were cultured in 1% O2 condition to mimic the hypoxic tumor microenvironment. The migrations of cancer cells were measured by transwell assay and scratch assay. Results: Rh2 could inhibit hypoxia-induced A549 and H1299 cell migration via increase of mir-491 expression. Further, mir-491 antisense oligonucleotide could repress hypoxia-induced migration and the expression of matrix metalloproteinase (MMP)-9 expression in Rh2-treated A549 cells. Conclusion: These findings suggest that Rh2 exerts anti-metastasis activity in the hypoxic tumor microenvironment in lung adenocarcinoma cells via mir-491.
Keywords: Ginsenoside Rh2